A Review of Tannins in Berries - Bernjak, Barbara; Kristl, Janja (Agricultura Scientia, 2021)
Tannins are a group of polyphenolic compounds synthesized and accumulated by higher plants as secondary metabolites. They are divided into hydrolysable tannins and proanthocyanidins and are found in many plant tissues in which they occur in diverse structures and amounts. This review provides a brief background on tannin distribution in plants, and summarizes the current literature on tannins in strawberries, raspberries, blueberries, currently the most commonly cultivated and consumed berries, and chokeberries, which have become popular in the last decades. The effects of processing and storage on tannin composition and levels in processed products are also provided.